Metode Design Thinking pada Sistem Informasi Alat Tulis Kantor (SIATK) Instansi Penanggulangan Bencana Karawang - Riska Mutiara; Eni Heni Hermaliani (LPPM STT Terpadu Nurul Fikri, 2025)
The management of office supplies at the Regional Disaster Management Agency in Karawang Regency is currently still carried out through direct verbal confirmation between employees and recorded using Excel, resulting in problems such as unsynchronized data, difficulty searching for old records, and a lack of integration into a single system, which is considered ineffective, inefficient, and in need of digitization of the office supply administration process. This study aims to design an ATK information system using Design Thinking, which consists of five stages: empathize, define, ideate, prototype, and test. This method is used to explore users' real needs, formulate problems accurately, generate ideas and solutions, and design and test interface designs. The tools used in the design were Google Forms for data collection from 48 respondents and Figma for creating the User Interface and User Experience designs and system prototypes. The results of this study show that the design thinking method is effective for designing an office stationery information system with a User Interface and User Experience prototype that can be understood and suits the needs of employees, thereby addressing the main problems in the ATK management process and providing a design basis that is ready for use in the next stage of system development.